Manufacture of medical orthopaedic implants using computed tomography imaging and rapid prototyping - Moayedfar, M. (Asian Research Publishing Network, 2016)
The manufacturing method of an orthopaedic implant using computed tomography image of the bone, current enhanced designs and rapid prototyping technology is studied to produce the mould of casting. This method can decrease the complexity of process and production time which as a great impact on medical metal implants manufacturing as compared to the usual approaches. The aim of this study is to integrate the function of 2D imaging, numerical solution, and rapid prototyping method for reducing many of the initial processes cost and time that is based on orthopaedic implants production. The integrated method of using 2D images to 3D part model is applied, and final part produced applying rapid prototyping machine. The comparative results illustrate a significant time reduction in some production steps which is almost near quarter of the current manufacturing process by employing the presented integrated system and rapid prototyping process. Â© 2006-2016 Asian Research Publishing Network (ARPN).